To solve \(3 \frac{2}{4} + 3 \frac{3}{4}\), we can first convert the mixed numbers to improper fractions.
-
Convert \(3 \frac{2}{4}\) to an improper fraction: \[ 3 \frac{2}{4} = \frac{3 \times 4 + 2}{4} = \frac{12 + 2}{4} = \frac{14}{4} \]
-
Convert \(3 \frac{3}{4}\) to an improper fraction: \[ 3 \frac{3}{4} = \frac{3 \times 4 + 3}{4} = \frac{12 + 3}{4} = \frac{15}{4} \]
Now we can add the two improper fractions: \[ \frac{14}{4} + \frac{15}{4} = \frac{14 + 15}{4} = \frac{29}{4} \]
Next, we can convert the improper fraction \(\frac{29}{4}\) back to a mixed number: \[ \frac{29}{4} = 7 \frac{1}{4} \]
Thus, the result of \(3 \frac{2}{4} + 3 \frac{3}{4}\) is: \[ \boxed{7 \frac{1}{4}} \]